A modular tension-adjusting splint for tendon transfer in reconstructive surgeries of extremities - B Kamath Jagannath; Bhardwaj Praveen (Indian Journal of Plastic Surgery)
Optimal tension during tendon transfer is the most important surgeon-controlled factor, which determines the final outcome of surgery. To attain optimal tension, the joints have to be maintained in proper position during the final attachment of the transferred tendon. Maintaining this desired position requires one extra assistant and is difficult. We herein describe a modular splint designed by us, which can be used for most of the commonly done tendon transfers in practice. It is very versatile as it can be used for all the age groups and for both right and left sides. A single splint, which is autoclavable and can be used for most commonly done tendon transfers, makes it user-friendly